2021
DOI: 10.1302/2058-5241.6.200052
|View full text |Cite
|
Sign up to set email alerts
|

The current state of robotics in total knee arthroplasty

Abstract: Robotic total knee arthroplasty (TKA) has demonstrated improved component positioning and a reduction of alignment outliers with regard to pre-operative planning. Early robotic TKA technologies were mainly active systems associated with significant technical and surgical complications. Current robotic TKA systems are predominantly semi-active with additional haptic feedback which minimizes iatrogenic soft tissue injury compared to conventional arthroplasty and older systems. Semi-active systems demonstrate adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 91 publications
0
39
0
Order By: Relevance
“…Thistechnique allows the surgeon to guidethe robotic arm to perform the bonypreparation, and thereforerequires constant input forthe procedure to be completed.Semi-active robotic systems enable surgeons tohavethe overall control for bone resection and implantpositioning. The image-freehandheld robotic sculpting system, Navio, was introduced in knee arthroplasties in 2017 [9]. This system does not require preoperative CT imaging, which is an advantageous point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thistechnique allows the surgeon to guidethe robotic arm to perform the bonypreparation, and thereforerequires constant input forthe procedure to be completed.Semi-active robotic systems enable surgeons tohavethe overall control for bone resection and implantpositioning. The image-freehandheld robotic sculpting system, Navio, was introduced in knee arthroplasties in 2017 [9]. This system does not require preoperative CT imaging, which is an advantageous point.…”
Section: Discussionmentioning
confidence: 99%
“…TheMako Robotic Arm Interactive Orthopaedic system (StrykerLtd, Kalamazoo, MI, USA) is an image-guidedsemi-active robotic system for RA-TKA. On the other hand, theNavioSurgical System (Smith & Nephew, Inc., Memphis, TN, USA) is an image-freehandheld robotic sculpting system introduced in knee arthroplasties in 2017 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Robotic systems are associated with high costs including the base system, operational costs, disposables, and preoperative imaging with an estimated initial start-up cost of approximately US$ 800,000 and recurring cost of $ 1500 per patient to implement and carry out surgical procedures and with disposable costing approximately between $ 750 and $ 1300. 10,38 Moreover, when image-based systems are used, preoperative imaging costs start from $ 260 and the annual maintenance costs for most robotic systems are between $ 40,000 and $ 150,000 and additional costs are required for the proper training of the surgical team. 39 Moschetti et al 39 reported that the robotic UKA system can be considered cost-effective in a high-volume setting of 100 cases annually, being case volume the most important determinant to the cost-effectiveness of the robotic system at the $ 50,000 willingness-to-pay (WTP) threshold, the most commonly used threshold used in the literature.…”
Section: Cost Effectiveness Analysismentioning
confidence: 99%
“…In the late 1980s, robotic systems began to be used in the operating room, with the first robotic-assisted TKA (roTKA) completed in 1988. Since then, the last decade has seen a surge in the number of roTKAs performed [ [2] , [3] , [4] ]. There are multiple factors contributing to the increase in popularity and utilization of roTKA including studies reporting improved accuracy in implant positioning and limb alignment, better short-term clinical outcomes, and increased patient-reported outcome measures (PROMs) with respect to the conventional manual technique [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%